Proposta de qualificaçao ambiental de uma área de lazer municipal - Lima, Carlos Eduardo de Almeida [UNESP]; Okimoto, Fernando Sérgio [UNESP]; Baptista, Camila Costa [UNESP]; Ribeiro, Camila Garcia Salles [UNESP]; Gandini, Daniela Prado [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper presents the process and results of the qualification proposal for a recreation area of the Presidente Prudente municipality that is currently in continuous and increasing degradation. The request came from members of the Cooperative College, neighbors of that area to the working group of the extension project "Technologies and Sustainable Buildings - Morumbi Building/FCT/UNESP", formed by three students of Architecture with scholarship of the "Adopt a Student" and a voluntary student the course of Architecture and Urbanism of Centro Universitário Toledo. The methodological approach of this study was the visits in the area, meetings with representatives of the Cooperative College and representatives of the Municipal Environment Secretariat (SEMA), to the definition of guidelines for the proposed development. After the definition of these guidelines and discussions between the workgroup, it was performed researches about these issues and then were presented ideas and suggestions to the Cooperative College. Therefore, it was possible to formulate a proposal to be submitted to the State Public Ministry of the Environment and the Municipal Department of the Environment.

O presente trabalho apresenta o processo e os resultados da proposta de qualificação de uma área de lazer da cidade de Presidente Prudente que atualmente se encontra em contínua e crescente degradação. A solicitação partiu de membros do Colégio Cooperativo, vizinhos da referida área, para o grupo de trabalho do Projeto de extensão “Tecnologias e Construções Sustentáveis - Núcleo Morumbi”, formado por três bolsistas do tipo “Adote um Aluno da UNESP” e uma aluna voluntária do curso de Arquitetura e Urbanismo da Faculdade Toledo de Ensino. A abordagem metodológica do trabalho foi a de visitas ao local, reuniões com representantes do Colégio Cooperativo e com representantes da Secretaria Municipal do Meio Ambiente, para a definição de diretrizes norteadoras do desenvolvimento da proposta. Após a definição de tais diretrizes e de discussões entre o grupo, realizadas pesquisas de fundamentação e depois foram apresentadas ideias e sugestões ao Colégio Cooperativo. A partir disso, foi possível formalizar uma proposta que será encaminhada ao Ministério Público Estadual do Meio Ambiente e para a Secretaria Municipal do Meio Ambiente. Portanto, apresenta-se como resultado do trabalho, uma proposta que qualifica os espaços da área de lazer que tem sido utilizada como local de descarte clandestino de resíduos.
Keywords: Environmental qualification; Environmental education; Sustainable technologies; Qualificação ambiental; Educação ambiental; Tecnologias sustentáveis